2022
DOI: 10.3390/jcm11102891
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Pancreatoduodenectomy: A Non-Trauma Center Case Series

Abstract: (1) Background: Emergency pancreatoduodenectomy (EPD) is a rare procedure, especially in non-trauma centers. Pancreatoduodenectomy is a challenging intervention, that has even higher risks in emergency settings. However, EPD can be a life-saving procedure in selected cases. (2) Methods: Our study is a single-center prospective consecutive case series, on patients that underwent emergency pancreatoduodenectomies in our surgical department between January 2014 to May 2021. (3) Results: In the 7-year period, 4 ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In the literature, EPD were rarely reported, and most were case reports or case series [1][2][3][4][5][6][7][8][9][10][11][12]. In this series, EPD accounted for just 2.2% of all cases of PD.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…In the literature, EPD were rarely reported, and most were case reports or case series [1][2][3][4][5][6][7][8][9][10][11][12]. In this series, EPD accounted for just 2.2% of all cases of PD.…”
Section: Discussionmentioning
confidence: 73%
“…In the literature, an EPD mortality rate of 0% to 40% was reported [1][2][3][4][5][6][7][8][9][10][11][12]. Gulla et al [6] reported a cumulative mortality rate of 29% for EPD from 1964 to 2013.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations